Pendidikan Akhlak Menurut Ibn Miskawaih dan Relevansinya terhadap Pendidikan Karakter Bangsa - Semin Semin (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2019)
The extraordinary development and explosion of science and information technology should also be accompanied by attention to education, especially moral education so that character education has lately been echoed as forming emotional intelligence of individuals, especially in the world of education being able to become a shield to be able to survive in the face of challenges of the times. Along with these problems Ibn Miskawaih in the book "Tahdzib Al Akhlaq Wa tathhir al A'raq" defines the value of moral education with a mental state that is able to encourage someone to do an act spontaneously, without the need for consideration and thought. The state of the soul (morals) is divided into two categories, namely: Innate from birth (heredity / naturalyah), and morality that is produced through the process of training and habituation. While character education has a goal to straighten out various negative child behaviors into positive ones. The alignment process which is interpreted as a behavior correction is understood as a pedagogical process, then accompanied by an exemplary school and home environment, and a habituation process. Therefore the relevance of the concept of Ibn Miskawaih Moral Education with Nation Character Education includes: 1. The objectives contained in the moral education according to Ibn Miskawaih and the goals contained in Nation Character Education are the formation of noble morals. 2. The methods and materials used by Ibn Miskawaih in the concept of moral education are also in accordance with those contained in Nation Character Education. This is the point of relevance between the two concepts, namely the objectives, methods, and curriculum.